KONSEP UNITED NATIONS GLOBAL COMPACT DALAM ISU HAK ASASI MANUSIA UNTUK TERWUJUDNYA CORPORATE SUSTAINABILITY - Muhammad Rafi Darajati; Muhammad Syafei (Law Faculty of Universitas Bandar Lampung, 2017)
The presence of multinational corporations as one subjects of international economic law has had a significant influence in international economic relations. A corporation certainly can give a big contribution in social, economic, and cultural progress. But, on the other side, we are also faced by many processes which bring adverse impact to societies, loss the sources of the society life or at more serious level is the violations of human rights in the sector of corporate activity. This article aims to see how the international community’s effort in issues related to the company in the business filed when dealing with human rights. One of efforts undertaken by the international community was made an initiative name with United Nations Global Compact. Author use juridical-normative research method with literature studies. According to the result of studies, can be seen that the ultimate goal of initiative is to create a sustainable world economy. By the presence of this initiative, we hope that businesses which run a multinational company may enforce the values and principles that have been established in United Nations Global Compact, on of which is the respect of human rights.